PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL PADA MATERI NILAI TEMPAT BILANGAN CACAH DI KELAS III SD NEGERI 01 WONOREJO - Devi Putri Rahayuningsih; Para Mitta Purbosari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the use of Wordwall learning media on the topic of place value of whole numbers in Grade III of SD Negeri 01 Wonorejo, Jatiyoso District, Karanganyar Regency, and to identify obstacles and solutions in its implementation. The study used a descriptive qualitative approach with research subjects consisting of 4 Grade III students, the class teacher, and the principal. Data collection techniques were carried out through source triangulation including observation, interviews, and documentation. The results showed that the use of Wordwall, particularly the Spin the Wheel feature, proved effective in increasing students' enthusiasm, active engagement, and understanding of place value concepts. Students demonstrated critical thinking skills, confidence in presenting answers, and good conceptual generalization abilities. Obstacles found included limited technological devices, lack of formal teacher training, and limited time to integrate the media comprehensively. The solutions were the use of projectors for classical learning, structured turn-taking, and direct teacher guidance. This study confirms that Wordwall is worthy of development as an interactive learning medium in elementary schools to support the implementation of the Merdeka Curriculum.